Beleza e mundo prático na filosofia de Hegel - Spadoni, Nicolau (Revista Eletrônica Estudos Hegelianos, 2021)
The present article aims to deal with the existing relation between beauty and practical world in Hegel’s philosophy through a consideration of a few topics that arise above all from the Outlines of the Philosophy of Right and the Lectures on Aesthetics, even though other Hegelian works are en passant also taken into account. Those topics will consist of 1) examining the relation between State and individuality in different moments of Hegel’s philosophy, 2) reconsidering the question of heroism and the age of heroes that arise in the Aesthetics and 3) comparing how the category of action comes into light in the Philosophy of Right as well as in the Aesthetics. Ultimately, our concluding remarks will try to advocate that the present investigation points out to the fact that a more thorough exam of the passage from right to art, from objective to absolute spirit, has to take into account the emergence of the concept of beauty in all its distinct determinations.